Storm-time convection dynamics viewed from optical auroras. (15th October 2019) - Yang, Bing; Donovan, Eric; Liang, Jun; Ruohoniemi, J. Michael; McWilliams, Kathryn; Spanswick, Emma
Abstract: A series of statistical and event studies have demonstrated that the motion of patches in regions of Patchy Pulsating Aurora (PPA) is very close to, if not exactly, E × B convection. Therefore, 2D maps of PPA motion provide us the opportunity to remotely sense magnetospheric convection with relatively high space and time resolution, subject to uncertainties associated with the mapping between the ionosphere and magnetosphere. In this study, we use THEMIS ASI (All Sky Imager) aurora observations combined with RBSP electric field and magnetic field measurements to explore convection dynamics during storm time. From 0500 UT to 0600 UT on March 19 2015, auroral observations across ~4 h of magnetic local time (MLT) show that increases in the westward velocities of patches are closely related to earthward flow bursts in the inner plasma sheet. Together with the meridian scanning photometer (MSP) data, this suggests that the increase in the westward velocities of PPA patches is caused by earthward-moving ion injection structures carried by the fast earthward flows. Highlights: Large scale convection dynamics were seen from optical auroras (from pulsating aurora to streamers). Increases in the westward velocities of pulsating aurora patches are closely related to earthward flow bursts in the inner plasma sheet. The increase in the westward velocities of patches is suggested to be caused by earthward-moving ion injection structures carried by the fast earthward flows.